Review artikel: analisis validasi metode penetapan kadar logam timbal (Pb) dalam kosmetik menggunakan berbagai instrumen - Razkianita, Haulya; Permatasari, Lina (Universitas Mataram, 2025)
Lead (Pb) is one of the most commonly found heavy metal contaminants in cosmetic products. Continuous exposure to lead (Pb) can cause pathological changes in body organs and may lead to cancer. Therefore, it is essential to measure the concentration of lead in cosmetics to ensure safety and prevent potential side effects. This article aims to determine the most effective method for analyzing lead (Pb) content in cosmetic preparations using various instruments, including UV-Vis Spectrophotometry and Atomic Absorption Spectrophotometry (AAS). This study was conducted by comparing the validation results of both instruments. The results showed that the lead (Pb) content in most cosmetic preparations was below the safety limit set by the Badan Pengawas Obat dan Makanan (BPOM) Indonesian, which is <20 ppm. Atomic Absorption Spectrophotometry (AAS) was selected as the most optimal method, as it met all validation parameters with high accuracy and precision. It also demonstrated higher sensitivity, with lower LOD (Limit of Detection) and LOQ (Limit of Quantification) values compared to UV-Vis Spectrophotometry. Therefore, AAS is superior in detecting and quantifying lead in cosmetic preparations